Science Education in Bangladesh: A Qualitative Review of Progress, Challenges, and Policy Prospects - Elias Ahmed; Saif Uddin Ahmed Khondoker; Mahmudulhassan Mahmudulhassan (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2025)
This study examines the situation of science education in Bangladesh, analyzing the effects of government changes and concentrating on the difficulties the educational system faces. The study is to shed light on curriculum, teacher preparation, and resource availability to enhance science education in both urban and rural settings. Semi-structured interviews, policy analysis, and a review of the literature were all part of the qualitative research methodology. In addition to interviews with elementary and secondary science teachers throughout Bangladesh, information was obtained from pertinent educational policies, scholarly publications, and reports. Teachers' opinions on the difficulties of teaching science, the availability of resources, and the efficacy of governmental reforms were all examined in the interviews. Recurring themes and patterns were found using thematic analysis. Results show that access to science education has increased, while there are still issues, especially in rural areas. Inadequate teacher preparation, a lack of resources, and an antiquated curriculum that impedes inquiry-based learning are major problems. Regional inequities and gaps in teacher skills persist despite government initiatives to promote digital education and infrastructure. To raise the standard of science education, the report emphasizes the necessity of ongoing investments in infrastructure upgrades, curricular reforms, and teacher development. A small sample size that might not accurately represent all regional contexts and possible bias in self-reported data are among the limitations. With its useful suggestions for resolving the issues and enhancing science instruction in Bangladesh, this study provides insightful information for researchers, educators, and policymakers.